FUYUANPERLEIDUS DENGI GENG ET AL., 2012 (OSTEICHTHYES, ACTINOPTERYGII) FROM THE MIDDLE TRIASSIC OF YUNNAN PROVINCE, SOUTH CHINA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Two well preserved specimens of Fuyuanperleidus dengi Geng et al., 2012 are described from the Upper Member of the Guanling Formation (Pelsonian, Anisian, Middle Triassic) in Luoping County, Yunnan Province, South China. The attribution  to Perleidiformes is confirmed according to a combination of features such as the general skull pattern, with the large preoperculum showing a prominent infraorbital process, the maxilla with deep posterior region and a dentition made of  long and stout peg-like teeth with an acuminate apex, the deep mid-lateral flank scales and the caudal fin with epaxial fin rays. However, this taxon shows an unique arrangement of the squamation (here considered as autapomorphy) given by the insertion of several scales in each vertical row posterior to the pelvic fin, just below the scales carrying the lateral line, when their depth decreases abruptly. Owing to this unique character, and  in spite of the very recent description of this genus, the authors considered necessary the erection of a new family, Fuyuanperleididae offering also new insights on the evolutionary trends and morphological specializations of the “subholosteans”. A cladistic analysis of the well known perleidiformes, with this taxon included, supports a possible monophyly of the order, and matches well the paleobiogeographic relationships of the Gondwana fresh-water taxa. The specialized deep-bodied Gondwana and Tethyan perleidiformes are independently evolved, ascertained by the parsimony analysis.
Keywords: Actinopterygians; Perleidiformes; Middle Triassic; South China